YouTube as a source of information on skin bleaching: a content analysis. (1st June 2018) - Basch, C. H.; Brown, A. A.; Fullwood, M. D.; Clark, A.; Fung, I. C.‐H.; Yin, J.
Summary: Background: Skin bleaching is a common, yet potentially harmful body modification practice. Aim: To describe the characteristics of the most widely viewed YouTube™ videos related to skin bleaching. Methods: The search term 'skin bleaching' was used to identify the 100 most popular English‐language YouTube videos relating to the topic. Both descriptive and specific information were noted. Results: Among the 100 manually coded skin‐bleaching YouTube videos in English, there were 21 consumer‐created videos, 45 internet‐based news videos, 30 television news videos and 4 professional videos. Excluding the 4 professional videos, we limited our content categorization and regression analysis to 96 videos. Approximately 93% (89/96) of the most widely viewed videos mentioned changing how you look and 74% (71/96) focused on bleaching the whole body. Of the 96 videos, 63 (66%) of videos showed/mentioned a transformation. Only about 14% (13/96) mentioned that skin bleaching is unsafe. The likelihood of a video selling a skin bleaching product was 17 times higher in internet videos compared with consumer videos (OR = 17.00, 95% CI 4.58–63.09, P < 0.001). Consumer‐generated videos were about seven times more likely to mention making bleaching products at home compared with internet‐based news videos (OR = 6.86, 95% CI 1.77–26.59, P < 0.01). Conclusions: The most viewed YouTube video on skin bleaching was uploaded by an internet source. Videos made by television sources mentioned more information about skin bleaching being unsafe, while consumer‐generated videos focused more on making skin‐bleaching products at home.